A bone regeneration repair patch and its preparation method and use
By using bone regeneration repair patches composed of dense layer, composite layer and pore-like layer in bone defect repair, the problem of difficulty in self-repairing of large segments of bone defects is solved, and the bone repair rate is improved and the treatment cycle is shortened.
Patent Information
- Application Number
- CN202411742014.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The prior art faces the problems of large segments of bone defect repair, long treatment cycles, and increasing the risk of infection and immune response disorders in bone defect repair.
The bone-promoting regeneration repair patch consisting of a dense layer, a composite layer and a pore-like layer is used. The composite layer is a slurry obtained by homogenizing the bone-promoting regeneration component. The dense layer and a pore-like layer are a decellular matrix material, and a multi-layer structure is formed by lyophilization and laser processing.
This patch enhances bone repair rate by shielding rapidly migrating soft tissue cells, promoting the clinging and invasion of osteoblasts, has excellent bone-promoting and regeneration performance, and simplifies the preparation process and reduces cost and time.
Smart Images

Figure CN119215232B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of pharmaceutical preparations, and in particular relates to a bone regeneration and repair patch, and a preparation method and use thereof. Background Art
[0002] Bone defect refers to the destruction of the integrity of bone structure due to trauma, infection, surgery, tumor resection, etc., resulting in local bone loss. This disease is very common in clinical practice and often causes bone nonunion, delayed healing or nonunion, and functional disorders. Bone defect repair, especially the repair of large bone defects, is a major problem in the orthopedic field. People have studied and applied a variety of methods to repair bone defects, mainly including bone transplantation, the use of hydroxyapatite / β-tricalcium phosphate coated scaffolds or hydrogel scaffolds to assist bone healing, etc. Despite the existence of a variety of treatment methods, the treatment of bone defects still faces many challenges. For example, large bone defects are often difficult to self-repair, the treatment cycle is long, and the risk of infection and immune response disorders is increased.
[0003] CN 114732962B discloses a degradable antibacterial guided bone regeneration membrane and its preparation method and application, which uses hydroxyapatite as a bone regeneration component. Due to the poor mechanical properties, slow degradation rate, single function, and lack of inducing bone regeneration and angiogenesis activity of hydroxyapatite, it cannot repair damaged bone tissue in a short time when used alone in bone tissue engineering. CN107029296A discloses a periosteum patch for guiding bone regeneration, its preparation method and application, which dries the matrix material of the small intestinal mucosa at 25-40°C for 8-16 hours to prepare a dense basal layer with low porosity, and then covers other components and uses vacuum freeze drying again. Its process is complicated and costly. In addition, studies have shown that as a bone regeneration repair patch, especially an absorbable repair patch, its degradation time cannot match the bone regeneration repair cycle, which will affect bone regeneration. Specifically, if the repair patch degrades too quickly, it will be difficult to maintain the bone regeneration space, thereby reducing the ability to guide bone regeneration, and it will not be able to isolate and prevent soft tissue cells from migrating too quickly; if it degrades too slowly, it will occupy the repair space of the bone and the tissue around the bone, reducing the repair rate. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a bone regeneration repair patch, which is composed of a dense layer, a composite layer and a porous layer, wherein the composite layer is located between the dense layer and the porous layer;
[0005] The dense layer and the porous layer are decellularized matrix materials;
[0006] The composite layer is a slurry obtained by homogenizing the decellularized matrix material and the bone regeneration promoting component;
[0007] The decellularized matrix material is decellularized small intestinal submucosa;
[0008] The bone regeneration promoting components include hydroxyapatite, decalcified bone matrix and bone morphogenetic protein.
[0009] Furthermore, the mass percentage of each raw material in the slurry is:
[0010] Decellularized matrix material 70-80%, hydroxyapatite 3-5%, decalcified bone matrix 10-15%, bone morphogenetic protein 0-1%, and the rest is water.
[0011] Furthermore, the mass percentage of each raw material in the slurry is:
[0012] Acellular matrix material 80%, hydroxyapatite 3-4%, decalcified bone matrix 10-15%, bone morphogenetic protein 0.1-1%, and the rest is water;
[0013] Or: decellularized matrix material 70%, hydroxyapatite 5%, decalcified bone matrix 15%, and the rest is water.
[0014] Furthermore, the mass percentage of each raw material in the slurry is:
[0015] Acellular matrix material 80%, hydroxyapatite 4%, decalcified bone matrix 15%, bone morphogenetic protein 1%.
[0016] Furthermore, the dense layer is 1 to 3 layers of decellularized matrix material; the porous layer is 1 to 2 layers of laser-treated decellularized matrix material; the composite layer is 0.2 to 0.3 g slurry / cm 2 .
[0017] Furthermore, the acellular matrix material is acellular porcine small intestinal submucosa; the bone morphogenetic protein is bone morphogenetic protein 2;
[0018] The decalcified bone matrix is defatted and decalcified porcine tibial plateau cancellous bone.
[0019] The present invention also provides a method for preparing the aforementioned bone regeneration and repair patch, comprising the following steps:
[0020] 1) Mix the decellularized matrix material, hydroxyapatite, decalcified bone matrix and bone morphogenetic protein, and blend them to obtain a slurry;
[0021] 2) Take the decellularized matrix material, apply the slurry obtained in step 1), cover the decellularized matrix material on the slurry, freeze-dry, and finally perform laser processing on one side of the decellularized matrix material to obtain the decellularized matrix material.
[0022] Furthermore, the mass percentage of each raw material in the slurry of step 1) is:
[0023] Acellular matrix material 80%, hydroxyapatite 3-4%, decalcified bone matrix 10-15%, bone morphogenetic protein 0.1-1%, and the rest is water;
[0024] Or: decellularized matrix material 70%, hydroxyapatite 5%, decalcified bone matrix 15%, and the rest is water.
[0025] Furthermore, in step 1), the decalcified bone matrix is defatted and decalcified porcine tibial plateau cancellous bone; the bone morphogenetic protein is bone morphogenetic protein 2; and the decellularized matrix material is decellularized porcine small intestinal submucosa.
[0026] Furthermore, in step 2), the side of the decellularized matrix material coated with the slurry is 1 to 3 layers of decellularized porcine small intestinal submucosa, and the side subjected to laser processing is 1 to 2 layers of decellularized porcine small intestinal submucosa;
[0027] The coating amount of the slurry is 0.2~0.3 g / cm 2 ;
[0028] The freeze-drying parameters are: heating to 35-40°C at 5°C / min, keeping warm for 6 hours; cooling to -35--30°C at 10°C / min, keeping warm for 6 hours; heating to 0°C at 5°C / min, keeping warm for 4 hours; heating to 10-15°C at 5°C / min, keeping warm for 4 hours; heating to 35°C at 10°C / min, keeping warm for 4 hours;
[0029] The parameters of the laser processing are: frequency: 200 khz, power 4 w, processing line spacing 8 mm, and processing times 8 to 22 times.
[0030] Finally, the present invention provides a use of the aforementioned bone regeneration promoting repair patch in preparing a drug for repairing bone defects.
[0031] The bone regeneration repair patch of the present invention is assembled together with a dense layer and a porous layer made of acellular matrix material by using a composite layer made of a specific raw material, and by using the adhesion of the composite layer slurry. By increasing the temperature of the pre-freeze-drying treatment and extending the treatment time, the high temperature plays a drying effect, and a dense layer with low porosity is obtained. The dense layer with low porosity has a good shielding effect, preventing soft tissue cells with a faster migration rate from entering the bone defect site; the holes in the porous layer prepared by laser enhance the looseness and roughness of the patch, so as to facilitate the attachment and infiltration of osteoblasts to occupy the bone-promoting space and enhance the osteogenesis effect; the sponge structure of the composite layer changes with the ratio within a certain proportion of raw materials to obtain different porosities and pore sizes, which can meet the infiltration and value-added of bone-promoting related cells of different sizes, thereby promoting the bone repair rate; the interaction of the multilayer structure makes it have excellent bone regeneration performance. At the same time, the preparation method of the present invention has fewer operating procedures, reduces the preparation time, improves the output efficiency, and has practical promotion and application value.
[0032] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0033] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Schematic diagram of the structure of the bone regeneration repair patch, where 1 is the dense surface; 2 is the composite layer; 3 is the porous layer; 4 is the pore structure of the porous layer;
[0035] Figure 2 This is a schematic diagram of the porous layer structure of the bone regeneration repair patch;
[0036] Figure 3 is a SEM image of the dense layer of the bone regeneration repair patch, wherein from left to right are sample 1-1, sample 1-2, and comparative sample 1-1;
[0037] Figure 4 This is the HE staining picture of the bone regeneration repair patch (photographed at 400x), where a) is the result of the fibroblast test; b) is the result of the epithelial cell test; the green arrow in the picture points to the cell nucleus;
[0038] Figure 5It is the SEM image of the composite layer of the bone regeneration repair patch; among them, a) sample 1-1; b) sample 1-3; c) sample 1-4; d) comparison sample 1-2; e) a representative broken, non-sponge-like sample among the comparison samples; f) a representative aggregated and clumped sample among the comparison samples.
[0039] Figure 6 This is a graph showing the results of cell proliferation and cell invasion of the bone regeneration repair patch. DETAILED DESCRIPTION
[0040] The raw materials and equipment used in the specific implementation of the present invention are purchased from the market. The decellularized porcine small intestinal submucosa involved is homemade, and commercially available ones can also achieve the same effect.
[0041] The decalcified bone matrix was homemade, and the raw material was porcine tibial plateau cancellous bone. It was prepared according to the method retrieved from the literature, specifically: the porcine tibial plateau cancellous bone was processed into bone blocks of 10 mm×10 mm×10 mm in size, which were repeatedly rinsed with 50°C water and drained; chloroform and methanol were mixed in a ratio of 1:1, the bone blocks were put into the mixture, and the bone blocks were defatted at room temperature for 24 h under stirring with a magnetic stirrer, then taken out for cleaning and air-drying; then the bone blocks were placed in a 0.6 M HCl solution for stirring and decalcification for 24 h, and the mixture was repeated twice. After the mixture was finished, the bone blocks were taken out for cleaning and air-drying.
[0042] Bone morphogenetic protein Bone morphogenetic protein 2 (BMP-2) was purchased from Yisheng Biotechnology (Shanghai) Co., Ltd.
[0043] Example 1 Preparation of a bone regeneration repair patch
[0044] (1) Preparation of decellularized matrix materials:
[0045] The pig small intestine was taken, and the mucosal layer, serosal layer and muscular layer were scraped off. After virus inactivation, fat removal, antigen removal and washing, the decellularized pig small intestinal submucosa, i.e., the decellularized matrix material, was obtained.
[0046] (2) Preparation of composite layer:
[0047] The decellularized matrix material obtained in the above step is mixed with the bone regeneration promoting component, and the mixture is blended to prepare a composite decellularized matrix homogenate slurry, wherein the bone regeneration promoting component is hydroxyapatite, decalcified bone matrix and bone morphogenetic protein; the mass percentages of the decellularized matrix material, hydroxyapatite, decalcified bone matrix and bone morphogenetic protein are 80%, 4%, 15% and 1%, respectively.
[0048] (3) Assembly:
[0049] The decellularized matrix material obtained in step (1) was spread in two layers in a freeze-drying plate, and then coated with the composite decellularized matrix homogenate slurry obtained in step (2). The coating amount of the slurry was 0.25 g / cm 2 , and again covering it with 2 layers of the decellularized matrix material obtained in step (1);
[0050] (4) Freeze-drying:
[0051] The sample obtained in step (3) is placed in a vacuum freeze dryer, and the freeze-drying parameters are set as follows: heating to 40°C at 5°C / min, and keeping warm for 6 hours; cooling to -30°C at 10°C / min, and keeping warm for 6 hours; heating to 0°C at 5°C / min, and keeping warm for 4 hours; heating to 10°C at 5°C / min, and keeping warm for 4 hours; heating to 35°C at 10°C / min, and keeping warm for 4 hours, and freeze-drying and dehydration is performed;
[0052] (5) Laser processing:
[0053] The freeze-dried sample was taken out, and one side of the decellularized matrix material was processed by laser, and the laser parameters were set as follows: frequency: 200 kHz, power 4 W, processing line spacing 8 mm, and processing times 22 times.
[0054] A bone regeneration repair patch sample 1-1 consisting of a dense layer, a composite layer and a porous layer was prepared. Figure 1 , 2 The chemical composition of the sample was tested and the results are shown in the following table:
[0055]
[0056] Example 2 Preparation of a bone regeneration repair patch
[0057] The difference between the preparation method in Example 1 is that the freeze-drying parameters in step (4) are set as follows: heating to 35°C at 5°C / min and keeping warm for 6 h; cooling to -35°C at 10°C / min and keeping warm for 6 h; heating to 0°C at 5°C / min and keeping warm for 4 h; heating to 15°C at 5°C / min and keeping warm for 4 h; heating to 35°C at 10°C / min and keeping warm for 4 h, and freeze-drying and dehydration are performed; other conditions and steps are the same as in Example 1, and bone regeneration repair patch sample 1-2 is obtained.
[0058] Example 3 Preparation of a bone regeneration repair patch
[0059] The difference from the preparation method in Example 1 is that in the preparation of the composite layer in step (2), the mass percentages of the decellularized matrix material, hydroxyapatite, decalcified bone matrix, and bone morphogenetic protein are 80%, 3%, 10%, and 0.1%, respectively, and the remaining percentages are supplemented with purified water; other conditions and steps are the same as in Example 1, and bone regeneration repair patch samples 1-3 are prepared.
[0060] Example 4 Preparation of a bone regeneration repair patch
[0061] The difference from the preparation method in Example 1 is that in the preparation of the composite layer in step (2), the mass percentages of the decellularized matrix material, hydroxyapatite, decalcified bone matrix, and bone morphogenetic protein are 70%, 5%, 15%, and 0%, respectively, and the remaining percentages are supplemented with purified water; other conditions and steps are the same as in Example 1, and bone regeneration repair patch samples 1-4 are prepared.
[0062] Example 5 Preparation of a bone regeneration repair patch
[0063] The difference from the preparation method in Example 1 is that in the preparation of step (5), the laser processing parameters are: frequency: 200 khz, power 4 w, processing line spacing 8 mm, processing times 15 times; other conditions and steps are the same as in Example 1, and bone regeneration repair patch samples 1-5 are prepared.
[0064] Example 6 Preparation of a bone regeneration repair patch
[0065] The difference from the preparation method in Example 1 is that in the preparation of step (5), the laser processing parameters are: frequency: 200 khz, power 4 w, processing line spacing 8 mm, processing times 8 times; other conditions and steps are the same as in Example 1, and bone regeneration repair patch samples 1-6 are prepared.
[0066] Comparative Example 1
[0067] The difference from the preparation method in Example 1 is that the freeze-drying parameters in step (4) are set as follows: cooling to -40°C at 5°C / min and keeping warm for 6 h; heating to 0°C at 5°C / min and keeping warm for 6 h; heating to 10°C at 5°C / min and keeping warm for 6 h; heating to 30°C at 5°C / min and keeping warm for 6 h, and freeze-drying and dehydration are performed; other conditions and steps are the same as in Example 1, and a bone regeneration repair patch comparison sample 1-1 is obtained.
[0068] Comparative Example 2
[0069] The difference from the preparation method in Example 1 is that in the preparation of the composite layer in step (2), the mass percentages of the decellularized matrix material, hydroxyapatite, decalcified bone matrix, and bone morphogenetic protein are 100%, 0%, 0%, and 0%, respectively; the other conditions and steps are the same as in Example 1, and the bone regeneration repair patch comparison samples 1-2 are prepared.
[0070] Comparative Example 3
[0071] The difference from the preparation method in Example 1 is that in the preparation of step (5), no laser processing product is used. Other conditions and steps are the same as in Example 1, and bone regeneration repair patch comparison samples 1-3 are prepared.
[0072] Comparative Example 4
[0073] On the basis of Example 3, in the preparation of the composite layer in step (2), the addition amount of hydroxyapatite was 0%, 6%, and 9% to prepare comparative samples 1-4-1, comparative sample 1-4-2, and comparative sample 1-4-3.
[0074] Comparative Example 5
[0075] On the basis of Example 3, in the preparation of the composite layer in step (2), the addition amount of decalcified bone matrix was 0%, 4%, 8%, and 16% to prepare comparative samples 1-5-1, 1-5-2, 1-5-3, and 1-5-4.
[0076] Comparative Example 6
[0077] On the basis of Example 3, in the preparation of the composite layer in step (2), the addition amount of bone morphogenetic protein was 0%, 0.05%, and 1.01% to prepare comparative samples 1-6-1, 1-6-2, and 1-6-3.
[0078] The beneficial effects of the present invention are described below by means of test examples:
[0079] Experimental Example 1 Test on the effect of different freeze-drying parameters on bone regeneration repair patch
[0080] 1. Test methods
[0081] Sample 1-1 prepared in Example 1, sample 1-2 prepared in Example 2, and comparative sample 1-1 prepared in Comparative Example 1 were sampled and tested as follows:
[0082] 1) Water content: Take 0.2 g of the product and weigh it to obtain m1, then use an oven to dry it to constant weight, and then weigh it to obtain m2. The water content calculation formula is as follows: [(m1-m2) / m1]×100%.
[0083] 2) Scanning electron microscopy (SEM): SEM images are taken after the sample is sprayed with gold.
[0084] 3) Cell invasion test: A 40×40 mm product was fixed on a sterile mold with only one side exposed, and 5×10 4The fibroblasts and epithelial cells of cells were placed in a CO2 incubator, 5% CO2, 37°C and cultured for 72 h. Then, trypsin was used to digest and sterile PBS was used to wash away the excess cells. After taking out the samples, they were embedded in paraffin, and HE staining was performed along the cross-section. After that, they were observed under a 400x microscope to record the cell infiltration.
[0085] 2. Test results
[0086]
[0087] According to the above table and Figure 3 , Figure 4 The results show that compared with the comparative sample 1-1, the water content of samples 1-1 and 1-2 is lower and the structure is denser ( Figure 3 ), the dense surface can completely block cell invasion ( Figure 4 ), to prevent soft tissue cells such as fibroblasts and epithelial cells from invading and occupying bone formation space, affecting the osteogenesis effect.
[0088] Experimental Example 2: Effect of different composite layer formulations on bone regeneration repair patches
[0089] 1. Test methods
[0090] Sample 1-1 prepared in Example 1, sample 1-3 prepared in Example 3, sample 1-4 prepared in Example 4, comparative sample 1-2 prepared in comparative example 2, comparative samples 1-4-1 to 1-4-3 prepared in comparative example 4, comparative samples 1-5-1 to 1-5-4 prepared in comparative example 5, and comparative samples 1-6-1 to 1-6-3 prepared in comparative example 6 were taken out and gold-sprayed on the composite layers, and SEM images were taken. Representative results are listed below.
[0091] 2. Test results
[0092]
[0093] According to the above table and Figure 5 The results showed that the composite layers of samples 1-1, 1-3 and 1-4 were sponge-like, and the pore size and porosity of the composite layer sponge structure changed accordingly with the change of the feed ratio of decellularized matrix material, hydroxyapatite, decalcified bone matrix and bone morphogenetic protein. Among them, the pore size and porosity of the composite layer of samples 1-1 and 1-3 were significantly improved due to the combined effect of hydroxyapatite, decalcified bone matrix and bone morphogenetic protein ( Figure 5 a~c).
[0094] The composite layers of Comparative Samples 1-2, Comparative Samples 1-4-1~1-4-3, Comparative Samples 1-5-1~1-5-4, and Comparative Samples 1-6-1~1-6-3 cannot present a sponge-like state. They are either broken and collapsed or aggregated. In addition, the porosity and pore size are too large or too small. Figure 5 d~f), which is generally not conducive to the attachment and invasion of osteoblasts to occupy the bone-promoting space.
[0095] Therefore, the raw materials of the composite layer, decellularized matrix material, hydroxyapatite, decalcified bone matrix and bone morphogenetic protein, need to be added in a certain percentage, specifically: 80% decellularized matrix material, 3-4% hydroxyapatite, 10-15% decalcified bone matrix, 0.1-1% bone morphogenetic protein, and the rest is water; or: 70% decellularized matrix material, 5% hydroxyapatite, 15% decalcified bone matrix, and the rest is water. Among them, 80% decellularized matrix material, 4% hydroxyapatite, 15% decalcified bone matrix, and 1% bone morphogenetic protein can meet the infiltration and proliferation of bone-related cells of different sizes and promote the potential of bone repair rate.
[0096] Experimental Example 3: Effect of different laser intensities on bone regeneration repair patches
[0097] 1. Test methods
[0098] Products were prepared according to the laser parameters set for sample 1-1 prepared in Example 1, sample 1-5 prepared in Example 5, sample 1-6 prepared in Example 6, and comparative sample 1-3 prepared in Comparative Example 1.
[0099] 1) Physical property test: Use a measuring tool to test the hole depth.
[0100] 2) Degradation performance test: Take 40×40 mm product for degradation test, specifically: place the product in collagenase K solution (3 mg / mL, 6 mL) and keep it at a constant temperature of 37°C. After 24 hours, take out the remaining product, elute, dry it to constant weight, and finally weigh it to calculate the degradation rate.
[0101] Degradation rate (%) = [(constant weight of sample before degradation - constant weight of sample after degradation) / constant weight of sample before degradation] × 100%.
[0102] 2. Test results
[0103]
[0104] As shown in the results in the table above, the degradation rate of the comparative sample 1-3 is the lowest, indicating that the bone regeneration repair patch is not easily degraded by enzymes after the laser processing step is missing. Comparing samples 1-1, 1-5, and 1-6, it can be seen that as the number of laser processing times on the porous layer increases, the degradation rate gradually increases. It can be seen that by adjusting the laser parameters to control the laser processing depth and adjust the product degradation rate, the controllable release of bone-promoting components can be achieved.
[0105] Test Example 4 Performance test of bone regeneration repair patch
[0106] 1. Test methods
[0107] Samples: Sample 1-1 prepared in Example 1, Sample 1-3 prepared in Example 3, Sample 1-4 prepared in Example 4, Sample 1-5 prepared in Example 5, Sample 1-6 prepared in Example 6, and Comparative Sample 1-3 prepared in Comparative Example 3.
[0108] Cell culture: A 40 × 40 mm sample was fixed on a sterile mold with only one side exposed, and 5 × 10 4 The osteoblasts were placed in a CO2 incubator with 5% CO2 and 37℃ for 72 h.
[0109] ① Cell proliferation test: The MTT method was used to detect the number of osteoblast proliferation, and the log 10 The data of cell proliferation induction of each sample were calculated and the final results were expressed as an increment compared with comparative samples 1-3.
[0110] ②Cell invasion test: Then use trypsin to digest and sterile PBS to wash away excess cells, then take out the sample after cell washing, embed it in paraffin, slice it along the cross section for HE staining, and then observe it under a 400x microscope to record the cell infiltration. Define the number of cells after proliferation of invasion comparison samples 1-3 as 100%, and calculate the results of other products.
[0111] 2. Test results
[0112] like Figure 6 As shown in the figure, the results of cell proliferation and cell invasion of the comparative products show that the use of laser processing to prepare through holes in the porous layer can enhance the proliferation ability of osteoblasts. Among them, compared with the comparative sample 1-3, the cell proliferation ability of sample 1-1 increased by 1.5 logarithms and the cell invasion ability increased by 410%, which may be due to the release of bone-promoting components; and it is shown that adjusting the cavity of the composite layer to an appropriate size is more conducive to cell invasion, so as to facilitate proliferation and differentiation.
[0113] In summary, the present invention uses a composite layer made of specific raw materials, and assembles the dense layer and the porous layer made of decellularized matrix materials together using the adhesion of the composite layer slurry to produce a bone regeneration repair patch that has a good shielding effect on soft tissue cells with a faster migration rate, while facilitating the attachment and invasion of osteoblasts to occupy the bone-promoting space, thereby enhancing the osteogenesis effect.
Claims
1. A bone regeneration repair patch, characterized in that: It is composed of a dense layer, a composite layer and a porous layer, wherein the composite layer is located between the dense layer and the porous layer; The dense layer and the porous layer are decellularized matrix materials; The composite layer is a slurry obtained by homogenizing the decellularized matrix material and the bone regeneration promoting component; The decellularized matrix material is decellularized small intestinal submucosa; The bone regeneration promoting components include hydroxyapatite, decalcified bone matrix and bone morphogenetic protein; The mass percentage of each raw material in the slurry is: Acellular matrix material 80%, hydroxyapatite 3-4%, decalcified bone matrix 10-15%, bone morphogenetic protein 0.1-1%, and the rest is water; Or: decellularized matrix material 70%, hydroxyapatite 5%, decalcified bone matrix 15%, and the rest is water.
2. The bone regeneration repair patch according to claim 1, characterized in that: The mass percentage of each raw material in the slurry is: Decellularized matrix material 80%, hydroxyapatite 4%, decalcified bone matrix 15%, bone morphogenetic protein 1%.
3. The bone regeneration repair patch according to claim 1, characterized in that: The dense layer is 1 to 3 layers of acellular matrix material; The porous layer is 1 to 2 layers of laser-treated decellularized matrix material; The composite layer is 0.2-0.3 g slurry / cm 2 .
4. The bone regeneration and repair patch according to any one of claims 1 to 3, characterized in that: The decellularized small intestinal submucosa is decellularized porcine small intestinal submucosa; The bone morphogenetic protein is bone morphogenetic protein 2; The decalcified bone matrix is defatted and decalcified porcine tibial plateau cancellous bone.
5. A method for preparing the bone regeneration repair patch according to claim 1, characterized in that: The steps include: 1) Mix the decellularized matrix material, hydroxyapatite, decalcified bone matrix and bone morphogenetic protein, and blend them to obtain a slurry; 2) taking the decellularized matrix material, coating it with the slurry obtained in step 1), then covering the decellularized matrix material on the slurry, freeze-drying, and finally laser processing one side of the decellularized matrix material to obtain; Step 1) The mass percentage of each raw material in the slurry is: Acellular matrix material 80%, hydroxyapatite 3-4%, decalcified bone matrix 10-15%, bone morphogenetic protein 0.1-1%, and the rest is water; Or: 70% acellular matrix material, 5% hydroxyapatite, 15% decalcified bone matrix, and the rest water; Step 2) The freeze-drying parameters are as follows: heating to 35-40°C at 5°C / min, keeping warm for 6 hours; cooling to -35--30°C at 10°C / min, keeping warm for 6 hours; heating to 0°C at 5°C / min, keeping warm for 4 hours; heating to 10-15°C at 5°C / min, keeping warm for 4 hours; heating to 35°C at 10°C / min, keeping warm for 4 hours.
6. The method according to claim 5, characterized in that: Step 1) The decalcified bone matrix is defatted and decalcified porcine tibial plateau cancellous bone; the bone morphogenetic protein is bone morphogenetic protein 2; and the decellularized matrix material is decellularized porcine small intestinal submucosa.
7. The method according to claim 5, characterized in that: Step 2) the side of the decellularized matrix material coated with the slurry is 1 to 3 layers of decellularized porcine small intestinal submucosa, and the side subjected to laser processing is 1 to 2 layers of decellularized porcine small intestinal submucosa; The coating amount of the slurry is 0.2-0.3 g / cm 2 .
8. Use of the bone regeneration-promoting repair patch according to any one of claims 1 to 4 in the preparation of a drug for repairing bone defects.
Citation Information
Patent Citations
Periosteal repair sheet for guiding bone generation as well as preparation method and application of periosteal repair sheet
CN107029296A
Cartilage repair material and preparation method thereof
CN103394126A
Oral repair membrane for guiding tissue regeneration, preparation method thereof and related kit
CN115025296A
Multilayer biological bone repair material as well as preparation method and application thereof
CN118662701A